2023
DOI: 10.55519/jamc-01-10493
|View full text |Cite
|
Sign up to set email alerts
|

Granular Cell Astrocytoma

Abstract: Granular cell astrocytoma (GCA) is a rare glial neoplasm composed of abundant granular cytoplasm gives immunoreactivity for GFAP and S100 stains. We report a case of GCA in a 64 years old male presented with history of fits, right sided weakness and loss of consciousness. The microscopy showed sheets of large cells with abundant eosinophilic granular cytoplasm. No high-grade features were seen. Its differential diagnosis includes most of the benign histiocytic conditions. Granular cell astrocytoma has an aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…They are an important component of the intermediate filaments that help cells resist mechanical loads [ 95 ]. Batool et al [ 96 ] found a strong correlation between the intensity of CK5\6 staining and the different stages of dysplasia. Additionally, this marker allows for the differentiation of healthy mucosa from dysplastic mucosa.…”
Section: Discussion Of Potential Immunohistochemical Biomarkers In Gr...mentioning
confidence: 99%
See 1 more Smart Citation
“…They are an important component of the intermediate filaments that help cells resist mechanical loads [ 95 ]. Batool et al [ 96 ] found a strong correlation between the intensity of CK5\6 staining and the different stages of dysplasia. Additionally, this marker allows for the differentiation of healthy mucosa from dysplastic mucosa.…”
Section: Discussion Of Potential Immunohistochemical Biomarkers In Gr...mentioning
confidence: 99%
“…Cell division and proliferation p53 [53][54][55]75,76,117], Ki-67 [56,[68][69][70][71][72][73][74][75][76], CD105 [73,74], p63 [39,42,117], CD31 [39], CD34 [43], cycD1 [42], VEGF [43], YAP, Np63 [59], stathmin [80], CDKN1A [53] Epithelial-mesenchymal transition CK5\6 [96], CK19 [98], β-catenin [103,104], N-cadherin [109], E-cadherin [104][105][106][107], TWIST [111], VIM [107,108], PDPN [115,117], MMP-9 [108] Cell death regulation Bcl-2 [123,124], PDCD4 [128], HSP27 [131], cornulin [134] Cellular metabolism HIF-1a [136], iNOS...…”
Section: Relation Of Biomarkers Examples Of Biomarkers For Grading Of...mentioning
confidence: 99%
“…The RBC surface of blood group A contains antigen A and the serum/plasma contains anti-B antibodies. Blood group A has been linked to a higher risk of HIV [ 10 , 11 ], HBV [ 11 ], HCV [ 12 ], COVID-19 [ 13 , 14 ], malaria, smallpox, enterotoxoid-mediated cholera, glue ear, capsular glaucoma, and heart disease, as well as a number of cancers, including gastric, breast, ovarian, cervical, leukemia (ALL), and leukemia of the pancreas[ 8 ], HCV related hepatocellular carcinoma (HCC)[ 15 ] Non-secretors of blood group A are linked to non-insulin-dependent diabetes, ankylosing spondylitis, Graves' disease, and coeliac disease [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gastro-duodenal ulcers associated with blood group O non-secretors [ 9 ]. However, Blood group O has a lower risk of HIV, HBV [ 10 , 11 ] HCV [ 12 ], COVID-19 infection [ 13 , 14 ], HCV related HCC [ 15 ] and TTIs [ 11 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 Cervical chyle leak often occurs as a complication following procedures such as neck dissection or esophagectomy, due to the anatomical course of the thoracic duct. 4,5 On the contrary, spontaneous cervical chyle leak occurs without any clear cause such as surgery or trauma, and it is an extremely rare condition with very few reports. 6,7 Here, we report a case involving the successful diagnosis and treatment of cervical chyle leak by intranodal lymphangiography using lipiodol in a patient with a spontaneously occurring subcutaneous mass on the left side of the neck.…”
Section: Introductionmentioning
confidence: 99%